Renoprotective Effect of Small Doses of Losartan and Enalapril in Patients with Primary Glomerulonephritis - Tylicki, Leszek; Rutkowski, Przemyslaw; Renke, Marcin; Rutkowski, Boleslaw (American journal of nephrology, 2002)
Background: The renin-angiotensin system is thought to be involved in progression of chronic renal diseases of both diabetic and nondiabetic origin. It is confirmed that angiotensin-converting enzyme inhibitors reduce urinary protein excretion (UPE) and attenuate the development of renal injury. The angiotensin II receptor blockers are an alternative class of drugs inhibiting the renin-angiotensin system activity with preliminarily confirmed renoprotective activity. However, there is lack of data concerning renoprotective action of very small doses of these drugs. Methods: Prospective, randomized, 3-month study of the effects of losartan 25 mg (n = 17) vs. enalapril 10 mg (n = 17) vs. combination of losartan 25 mg and enalapril 10 mg (n = 15) on proteinuria, kidney function and metabolic profile in 51 patients with biopsy proven chronic glomerulonephritis with normal or slightly declined kidney function [creatinine clearance (CRCL) between 36 and 93 ml/min] was performed. Clinical evaluation and laboratory tests were estimated before treatment (basal), during the first week and after 3 months of therapy. Results: Both, monotherpy with losartan and enalapril significantly reduced proteinuria by 25.35 and 45.07%, respectively. There was no significant difference between groups. Combined therapy induced a more remarkable reduction of proteinuria (65.96%) than either of the drugs administered alone. This antiproteinuric effect was significantly more pronounced only in comparison with the losartan group (p = 0.009). Decreasing of blood pressure was most pronounced in the combined group. In all groups, no correlation between fall of UPE and reducing the systolic or diastolic blood pressure was found. Significant decline in CRCL was observed with enalapril treatment just after 1 week of therapy (p = 0.039) and at the end of observation (p = 0.043). CRCL remained stable in losartan-treated subjects. No changes in serum creatinine level, metabolic profile and sodium excretion were observed during therapy in studied groups. Conclusions: These results indicated that even very small doses of losartan and enalapril reduce proteinuria in patients with primary glomerulonephritis. Combination of these drugs could cause significantly greater antiproteinuric effect than either of the agents in monotherapy. It is likely that the treatment with losartan, compared to enalapril, is associated with less risk of acute fall of glomerular filtration at the beginning of therapy.